Fetal head position and perineal distension associated with the use of the BD Odon Device™ in operative vaginal birth: a simulation study. (21st September 2017) - O'Brien, SM; Winter, C; Burden, CA; Boulvain, M; Draycott, TJ; Crofts, JF
Abstract : Objective: To investigate (1) the placement of the BD Odon Device on the model fetal head and (2) perineal distention during simulated operative vaginal births conducted with the BD Odon Device. Design: Observational simulation study. Setting: North Bristol NHS Trust, UK. Population or sample: Four hundred and forty simulated operative vaginal births. Methods: Three bespoke fetal mannequins were developed to represent (1) bi‐parietal diameter of the 50th centile at term, (2) bi‐parietal diameter at the 5th centile at term, and (3) 50th centile head with 2 cm of caput. Siting of the BD Odon Device on model heads was determined before and after 400 simulated operative vaginal births. Variables were analysed to determine their effect on device siting and movement during birth. The fetal mannequins were placed inside a maternal mannequin and the BD Odon Device was placed around the fetal head as per the instructions for use. The location of the air cuff was determined before and after the head was delivered. Perineal distension was determined by recording maximum perineal distention during a simulated operative vaginal birth using the same procedure, as well as scenarios employing an inappropriately non‐deflated air cuff (for the BD Odon Device), the Kiwi ventouse and non‐rotational forceps. Main outcome measures: Site and displacement during birth of the BD Odon Device on a model head. Maximal perineal distension during birth. Results: The BD Odon Device was reliably sited in a standard over the fetal head position (approximately 40 mm above the fetal chin) for all stations, head sizes and positions with no significant displacement. In occipito‐posterior births, compared with occipito‐anterior or transverse, the BD Odon Device routinely sited further down the fetal head (toward the chin). The BD Odon Device was not associated with more perineal distension compared with forceps or Kiwi ventouse (respectively 21, 26 and 21 mm at posterior fourchette). Conclusions: The BD Odon Device reliably sited over a safe area of the fetal head in 400 simulated births representative of clinical practice. The BD Odon Device generates similar levels of perineal distension compared with Kiwi ventouse when used correctly. Tweetable abstract: Location of the BD Odon Device on a fetal head in simulation Tweetable abstract: Location of the BD Odon Device on a fetal head in simulation